2018
DOI: 10.1101/295501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diverse progenitor cells preserve salivary gland ductal architecture after radiation induced damage

Abstract: The salivary gland ductal network is maintained during homeostasis and after genotoxic injury by diverse progenitors that respond differentially to radiation induced damage. AbstractThe ductal system of the salivary gland has long been postulated to be resistant to radiationinduced damage, a common outcome incurred by head and neck cancer patients receiving radiotherapy. Yet, whether the ducts are capable of regenerating after genotoxic injury, or if damage to ductal cells induces lineage plasticity, as has be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…SGPCs maintain SG homeostasis by proliferation and differentiation [ 11 ]. The BSD is a proposed niche of SGPCs, and is easily identifiable histologically [ 12–14 ]. p16 + BSD and total epithelial cells in pSS significantly increased compared with non-SS sicca control patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SGPCs maintain SG homeostasis by proliferation and differentiation [ 11 ]. The BSD is a proposed niche of SGPCs, and is easily identifiable histologically [ 12–14 ]. p16 + BSD and total epithelial cells in pSS significantly increased compared with non-SS sicca control patients.…”
Section: Discussionmentioning
confidence: 99%
“…The basal striated duct (BSD) layer has been proposed to represent a progenitor cell niche in SG [ 11 ]. SG progenitor cells (SGPCs) that potentially reside in this niche maintain SG homeostasis by self-renewal and differentiation into other terminal and functional cell types in SGs, namely saliva producing acinar cells, saliva modifying ductal cells and myoepithelial cells [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We next searched for co-expression of selected genes in the mouse brain by histological methods. We chose the Kit gene for immunohistochemical analysis as highly specific antibodies for the cKit receptor are available ( May et al , 2018 ) and determined that virtually all PV-immunopositive neurons were also cKit-positive in the mouse ST. On the other hand, only a small proportion of striatal cKit-positive cells were PV-negative ( Fig. 5A; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lineage tracing has been used to determine the in vivo potential of several proposed stem cell populations in the adult salivary glands . Under normal physiological conditions, the proposed K5‐expressing and K14‐expressing stem cell populations labeled only duct cells . However, K14 cells undergo continuous cycling in vivo, contribute to differentiated cells in the granular ducts, and retain label after 28 weeks, indicating that they are a lineage‐restricted unipotent stem cell population .…”
Section: In Vivo Lineage Tracingmentioning
confidence: 99%
“…However, K14 cells undergo continuous cycling in vivo, contribute to differentiated cells in the granular ducts, and retain label after 28 weeks, indicating that they are a lineage‐restricted unipotent stem cell population . Lineage tracing also revealed that potential stem cells expressing c‐KIT and Wnt‐responsive Axin2 are restricted to generating duct cells in adult. In contrast to these results, lineage tracing of p63‐positive cells, which contribute to all salivary gland cell lineages during embryonic development, labeled a small number of acinar cells, in addition to duct and myoepithelial cells .…”
Section: In Vivo Lineage Tracingmentioning
confidence: 99%